Imaging Review of Hockey-related Lower Extremity Injuries - Holmes, R. Davis; Yan, Yet Yen; Mallinson, Paul I; Andrews, Gordon T; Munk, Peter L; Ouellette, Hugue A (Seminars in Musculoskeletal Radiology, 2022)
Hockey is a fast-paced contact sport with a high incidence of injuries. Although injuries are more frequent among elite players, recreational hockey injuries are a common issue faced by primary care and emergency physicians. Lower extremity injuries in hockey are particularly important because they account for approximately a third of all injuries and > 60% of all overuse injuries. This pictorial review provides the general and specialty trained radiologist with a knowledge of the patterns of lower extremity injury that occur in ice hockey.
Keywords: sports imaging; hockey; magnetic resonance imaging; lower extremity injuries